ANALISIS PENGARUH FASILITAS DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN PADA OBJEK WISATA PULAU ANGSO DUO KOTA PARIAMAN - Zella Permata Bunda; Septria Susanti (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to analyze the influence of facilities and word of mouth on tourists' visiting decisions at the Angso Duo Island tourist attraction, Pariaman City. The method in this research is quantitative using data analysis techniques, namely research instrument testing, classical assumption testing, multiple linear regression testing, hypothesis testing (t test and f test), and coefficient of determination testing. The sample used was 100 tourists who were used as respondents. The research results show that the results of the t test and F test obtained a significant value of 0.000 < 0.05, thus the Facilities variable (X1) and the Word of mouth variable (X2) have a positive and significant influence on Visiting Decisions (Y). And the R- Square value is 0.246 or 24.6%, which shows that the influence of facilities and word of mouth is 24.6% on tourists' visiting decisions.